Influence of the polarization in grazing scattering of fast helium atoms from LiF(001) surfaces - Gravielle, Maria Silvia (2008)
Grazing scattering of neutral atoms from insulator surfaces is investigated in the intermediate velocity range, in which interference effects have recently been observed. To describe this process we introduce a distortedwave method based on the use of the eikonal wave function, which takes into account the phase of the scattering state along the classical projectile path. The eikonal theory is applied to evaluate the angular distribution of few-keV helium atoms after impinging on a LiF 001 surface along low-index crystallographic directions. The interest focuses on the role played by the projectile polarization produced by cations and anions of the crystal surface. For the considered collision system we found a polarization channel, corresponding to the direction 110 , which is affected by this effect, while for incidence in the direction 100 the polarization contribution is nearly negligible. The proposed eikonal approach, including polarization effects, provides angular projectile spectra in good agreement with the experimental data.